Microbiota and probiotics - Corpino, Mara (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2017)
Microbiota, the collection of microorganisms peacefully coexisting with their human host, colonize virtually every surface of the human body exposed to the external environment. The complex community of microorganisms living in the digestive tract, the gut microbiota, is determined by the delivery mode, prematurity, sex, genetics and subsequent environmental exposures (diet, drugs). It has also been claimed that the constant interaction between the host and the gut microbiota influences the health of the host. Probiotics are defined as live non-pathogenic microorganisms that, when administered in adequate amounts can replicate and colonize in sufficient numbers the gastrointestinal tract. This is the main reason for the use of probiotics in different clinical settings where they may act as biomodulators of the intestinal microbiota. The therapeutic efficacy of probiotics has been evaluated in randomized controlled trials for various diseases. In this paper, the usage and the efficacy of probiotics in different conditions like necrotizing enterocolitis, sepsis, diarrhea, functional gastrointestinal disorders, inflammatory bowel disease, allergies are analyzed. The usefulness of a probiotic treatment is affected by many factors including: bacterial strain, duration of administration, disease and age and not all products marketed as probiotics provide the same safety and efficacy. Therefore, comparative studies to assess the most effective formulations, timing and the optimal length of therapy are mandatory.